Extensão em agroecologia: grupo CATAIA - Pedroso, Camila Pinto [UNESP]; Almeida, Luis Carlos Ferreira de [UNESP]; Alves, Amanda Sellarin [UNESP]; Pagassini, Jonas Akenaton Venturineli [UNESP]; Barduco, Analice Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The public policies for family farming has emphasized the need for the adoption by this sector of agriculture ecological bases. Since 2011, a group of students of UNESP Campus Registro Experimental, believing it necessary to discuss this scenario created a Agroecology Group, integrating teaching and research and extension, has been working this issue. This discussion is theoretical basis as making a critical analysis of current agricultural processes, which were not implemented by demand from farmers and social movements, but by the dominant sectors of agriculture, while proposing the change of production paradigms agricultural and rural development. The free access proposed by the group allows different actors involved in the processes of family farming and agroecology have access to areas of training and information, as well as the research and educational work carried out by the extension "Cataia".

As políticas públicas atuais voltadas para a agricultura familiar têm dando ênfase na necessidade da adoção, por este setor, de uma agricultura de bases ecológicas. Desde 2011, um grupo de alunos do Centro Acadêmico da UNESP Campus Experimental de Registro, sentindo a necessidade de discutir esse cenário formaram um grupo de Agroecologia no qual, integrando ensino-pesquisa e extensão, vem trabalhando esse assunto. Essa discussão encontra fundamentação teórica na medida que faz uma análise critica dos atuais processos agrícola, os quais foram implantados não pela demanda dos movimentos sociais e agricultores, mas por parte dos setores dominantes da agricultura, e ao mesmo tempo propõe a mudança dos paradigmas da produção agrícola e do desenvolvimento rural. O caráter de livre acesso proposto pelo grupo permite que diferentes atores envolvidos nos processos da agricultura familiar e da agroecologia tenham acesso aos espaços de formação e informação, assim como aos trabalhos de ensino pesquisa e extensão realizados pelo “CATAIA”.
Keywords: Extension; Study group; Family farming; Extensão rural; Grupo de estudo; Agricultura familiar